2006
DOI: 10.1002/tea.20159
|View full text |Cite
|
Sign up to set email alerts
|

Teaching nature of science through inquiry: Results of a 3‐year professional development program

Abstract: This study assessed the influence of a 3-year professional development program on elementary teachers' views of nature of science (NOS), instructional practice to promote students' appropriate NOS views, and the influence of participants' instruction on elementary student NOS views. Using the VNOS-B and associated interviews the researchers tracked the changes in NOS views of teacher participants throughout the professional development program. The teachers participated in explicitreflective activities, embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
0
26

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 260 publications
(205 citation statements)
references
References 33 publications
(32 reference statements)
13
166
0
26
Order By: Relevance
“…Previous studies on science professional development programs provide important insights into aspects such as designing appropriate lessons, adopting effective teaching methods, following particular instructional activities, and evaluating student learning (e.g., Akerson & Hanuscin, 2007;Luera & Otto, 2005). However, one limitation of these programs is that they often overlook the social dimension of science teaching (Oliveira, 2009;Oliveira, 2010) and the integration into instruction (e.g., Borko, 2004;Clarke & Hollingsworth, 2002;Yilmaz-Tuzun, 2008).…”
Section: Research Questionsmentioning
confidence: 99%
“…Previous studies on science professional development programs provide important insights into aspects such as designing appropriate lessons, adopting effective teaching methods, following particular instructional activities, and evaluating student learning (e.g., Akerson & Hanuscin, 2007;Luera & Otto, 2005). However, one limitation of these programs is that they often overlook the social dimension of science teaching (Oliveira, 2009;Oliveira, 2010) and the integration into instruction (e.g., Borko, 2004;Clarke & Hollingsworth, 2002;Yilmaz-Tuzun, 2008).…”
Section: Research Questionsmentioning
confidence: 99%
“…Challenges connected to NOS teaching have been thoroughly investigated and has contributed explanations as to why there is a perceived gap between research intentions and classroom practice (e.g., Abd-El-Khalick et al 1998;Akerson and Hanuscin 2007;Brickhouse and Bodner 1992;Clough and Olson 2012;Lakin and Wellington 1994;Hodson 1993;Höttecke and Silva 2011;Leden et al 2015;Lederman 1995). In other articles (Leden et al 2015;Leden and Hansson 2017), we have reported on, and argued that, teachers' perspectives constitute an important part in the attempt to understand and examine this gap further.…”
Section: Discussionmentioning
confidence: 85%
“…& A lack of teaching resources that can be embraced as adequate by the teachers (Abd-El- Akerson and Hanuscin 2007;Hanuscin et al 2011;Lakin andWellington 1994, Höttecke andSilva 2011) & NOS considered as an add-on even by teachers who regard it as important (Abd-El- Clough and Olson 2012;Höttecke and Silva 2011) & Teachers are unaccustomed to, and insecure regarding, the NOS teaching format and strategies (Bell et al 2000;Herman et al 2013;Lakin and Wellington 1994, Henke and Höttecke 2015, Leden et al 2015 & Concerns for students' abilities to deal with abstract or controversial issues (Abd-El- Aikenhead 2006;Brickhouse and Bodner 1992;Hodson 1993;Lederman 1995;Leden et al 2015) & Concerns for the Bgood students^who are accustomed to memorize facts for the test (Aikenhead 2006;Leden et al 2015) Research studies have examined what teachers perceive as opportunities with NOS teaching to a surprisingly small extent. One interesting exception is Herman et al (2015) who connected the Btype of utility value^expressed by the teachers to their level of NOS implementation.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The INSEP program can bring a positive impact for science content, teachers' PCK and efficacy as well as its correlation with the inquiry. The internalization of inquiry plays an important role in connecting teachers' understanding of nature of science and the instructional strategy in their class, and also crucial for teachers in developing their paradigm in improving their professionalism [20,21]. INSEP integrated with the inquiry process through learning simulation enables teachers to build the understanding of science as well as gaining the knowledge of instructional strategy of inquiry-based learning.…”
Section: Resultsmentioning
confidence: 99%